“Plan de comercialización de panela y miel de la Asociación “ASOPROMONCA” de la parroquia Pucayacu, cantón La Maná. - Chiguano Chusin, Damaris Izamar (2023)
A marketing plan is a strategic tool that describes a company, organization, and association. The "ASOPROMONCA" Association of the Pucayacu parish in La Maná canton was considered for the study. The objective is to develop a marketing plan to position and increase sales of its main products, such as raw cane sugar and honey. The main problems of the association are related to the low quality of the product, few marketing channels, and a low market share at the national level. The direct beneficiaries of the research will be the 15 members and 5 employees of the Association "ASOPROMONCA" the indirect beneficiaries will be the population of the Pucayacu parish, the Internal Revenue Service (SRI), the Municipal Government of La Maná and the Fire Department. The type of research is exploratory and descriptive with a qualitative and quantitative approach. The strengths, opportunities, weaknesses, and threats were applied to understand the current situation of the association and contribute to decision-making and competitiveness. The study population was the members and a Likert scale questionnaire and an interview were used. The results indicate the lack of a marketing plan in the "ASOPROMONCA" Association, while 33% of the partners do not know the marketing plan, and 67% have little knowledge. The business brand will call the "ASOPROMONCA" Association to commercialize raw cane sugar and honey. In a proposal designed for the business axis of the price strategy, Thompson (2017) states that by the application the marketing plan based on the price strategy helps the initial and final pricing of products and the positioning of the products increasing approximately 30% of the customers. The impact that the research project will have is: environmental, economic, and financial all this will guide the decision-making within the association. The proposal focuses on a marketing strategy for the positioning and loyalty of its external clients.